Evaluation of the Light/Dark Cycle and Concentration of Tannery Wastewater in the Production of Biomass and Metabolites of Industrial Interest from Microalgae and Cyanobacteria (2022)
The tanning industry transforms animal skins into leather and produces liquid effluents with a high organic and inorganic pollutant load. This work evaluated the effect of the tannery wastewater (TWW) concentration and the light/dark cycle on the production of biomass, carbohydrates, proteins, lipids, and pigments (carotenoids and phycobiliproteins) on two microalgae (Chlorella sp. and Scenedesmus sp.) and one cyanobacterium (Hapalosiphon sp.). A non-factorial central experimental design with a response surface was implemented using the STATISTICA 7.0 software. High removal percentages for nitrates (97%), phosphates (73.3%), and chemical oxygen demand (93.2%) were achieved with the three strains. The results also highlight that the use of a constant light regime (24:0) and the concentration of real TWW affect the biomass production, since the highest concentration of biomass recorded was 1.31 g L−1 of Hapalosiphon sp. with 100% undiluted wastewater.